The Authenticity of Qur’anic Codification: A Critique of Theodor Noldeke's Perspective - Zubaidi, Sujiat; Asnawi, Aqdi Rofiq; Fikriyah, Asfa (Fakultas Adab and Humaniora, Universitas Islam Negeri (UIN) Syarif Hidayatullah Jakarta, 2024)
PurposeThis research aimed to reveal the integrity of Utsman bin Affan and the authenticity of the Qur'an by the three parameters of integrity: Honesty, Consistency, and Courage, and three parameters of authenticity: Continuity, credibility, and symbolism. It also involved the criticism study of Theodor Noldeke’s View about the codification of The Qur’an. MethodThis research employed a qualitative library approach to analyze Theodor Noldeke's views on the codification of the Qur'an. The analysis method consists of two steps: first, a descriptive analysis of Noldeke's intellectual background and the concepts of integrity and authenticity; second, a comparative analysis of the codification of the Qur'an from the perspectives of Muslim and Western scholars. Results/findingsThere were integrity factors in Utsman bin Affan, namely honesty and trustworthiness in behaviour, consistency in action, and courage and responsibility in making decisions. Utsman bin Affan was a caliph with integrity, so all the policies he issued towards the codification of the Qur'an guaranteed authenticity. ConclusionAlthough Theodor Noldeke argued that the Qur'an codification policy of Utsman bin Affan was inauthentic and has many problems with it, this statement was considered incorrect due to differences in research methods used, as well as differences in the history of the Qur'an and the Bible.